2017
DOI: 10.1177/1351010x17709986
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing egg cartons’ sound absorption coefficient with recycled materials

Abstract: Egg cartons have popularly been used as sound absorbers because they are inexpensive, easy to install and easily available. However, acoustic experts have demonstrated that egg cartons are bad sound absorbers. This study developed Enhanced Egg Carton-Dry and Enhanced Egg Carton-Wet using additional recycled materials (shredded rice straw paper, textile waste, 2-cm cut rice straws) to improve the cartons' sound absorption coefficient while retaining their original advantages. Enhanced Egg Carton-Dry and Enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In fact, egg-boxes are made with different materials including plastic, recycled paper, cardboard and expanded polystyrene. Even though mainly the acoustic performance of egg-boxes has been investigated in the literature [34,102,103], several studies focused on their mechanical properties [104][105][106]. Egg-boxes' mechanical properties are more affected by shape than material [104], and greater mechanical resistance belongs to cardboard (even if strongly affected by humidity), followed by polystyrene and expended polystyrene [105].…”
Section: Egg-boxes and Traysmentioning
confidence: 99%
“…In fact, egg-boxes are made with different materials including plastic, recycled paper, cardboard and expanded polystyrene. Even though mainly the acoustic performance of egg-boxes has been investigated in the literature [34,102,103], several studies focused on their mechanical properties [104][105][106]. Egg-boxes' mechanical properties are more affected by shape than material [104], and greater mechanical resistance belongs to cardboard (even if strongly affected by humidity), followed by polystyrene and expended polystyrene [105].…”
Section: Egg-boxes and Traysmentioning
confidence: 99%
“…Egg-boxes and trays can be made of different materials such as plastic, recycled paper, cardboard, but what distinguishes them is their shape. For a long time, egg-cartons have been considered good sound absorbing materials, and they have been widely used for this purpose since they are inexpensive, easy-to-install and easily available [50]. However, their acoustic performances have been recently questioned.…”
Section: Egg-boxes and Traysmentioning
confidence: 99%
“…A non-standardized test method showed that filling egg-boxes with mineral wool blocks a percentage of sound ranging between 14.42% and 17.71% depending on the frequency. Egg-boxes were filled with shredded rice straw paper and textile waste [50], and with polyurethane foam [52]. The panels proposed in [50] showed higher sound absorption coefficients than common egg-boxes cartons at all frequencies, and those presented in [52] featured a NRC equal to 0.87.…”
Section: Egg-boxes and Traysmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most striking cases of designing packaging also considering its reuse is the one proposed by Heineken [7], which realized square glass bottles that were used to build houses in the Caribbean islands. Also the scientific community has realized the potential of end-of-life materials [8], and several studies have investigated the properties of plastic bottles [9,10], cardboard and paper elements [11][12][13][14][15][16], Tetra-Pak panels [17], textiles waste [18][19][20][21][22], and egg boxes and trays [23][24][25][26][27][28]. More recently, so-called green and sustainable materials made of natural fibers have been investigated [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%